Term structures of asset prices and returns - Backus, David; Boyarchenko, Nina; Chernov, Mikhail (Journal of Financial Economics, 2018)
We explore the term structures of claims to a variety of cash flows, namely, US government bonds (claims to dollars), foreign government bonds (claims to foreign currency), inflation-adjusted bonds (claims to the price index), and equity (claims to future equity indexes or dividends). The average term structures reflect the dynamics of the dollar pricing kernel, cash flow growth, and the interaction between the two. We use an affine model to illustrate how these two components can deliver term structures with a wide range of levels and shapes. Finally, we calibrate a representative agent economy to show that the evidence is consistent with the equilibrium models.